The Influence of Economic Factors on Investment Decisions in Property & Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Dina Oktavia; Fiya Lailatin Nisfi; Ario Purdianto (Jurnal Informasi dan Teknologi, 2025)
This study aims to determine the effect of economic factors on investment decisions, especially in property and real estate companies listed on the Indonesia Stock Exchange for 2020-2023. The financial factors that are the focus of this research are inflation and interest rates, with investment decisions proxied by the Price Earning Ratio (PER). The sample in this study consisted of 8 companies selected using a non-probability sampling method with a purposive sampling technique. Meanwhile, the research population includes all property and real estate companies listed on the Indonesia Stock Exchange, including as many as 94 companies. The method used in this research is a quantitative method with an associative approach. Data analysis was carried out using multiple linear regression techniques to measure the effect of inflation and interest rates on investment decisions. The results showed that inflation positively and significantly influences investment decisions as measured by Price Earning Ratio (PER). This means that an increase in inflation drives an increase in PER, which indicates that investors still have optimism about the prospects for investment in the property and real estate sector despite inflationary pressures. Conversely, interest rates have a positive and significant effect on investment decisions, which means that an increase in interest rates causes a decrease in PER. This shows that when interest rates increase, investors tend to shift their investments to safer instruments, thereby reducing interest in property and real estate stocks.